Analisis Kinerja Keuangan Dinas Sosial Kota Prabumulih Dengan Variabel Keuangan Dan Non Keuangan - Supriadi; Marjohan (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
This study aims to analyze the financial performance of the Prabumulih City Social Service both from financial and non-financial variables. In this study, the key informants were the leaders and employees of the Prabumulih City Social Service and the people who used the services of the Prabumulih City Social Service. The data analysis technique used is descriptive quantitative. The results showed that the financial performance of the Prabumulih City Social Service Office based on the balance scorecard assessment had all gone well. This can be seen from the financial assessment from 2019-2021. The results of the realization of the Prabumulih City Social Service budget realization activity were very good with the classification of the difference (variant) in the category of profitable difference. Then the non-financial assessment in terms of customer perspective, internal business process perspective and learning and growth perspective are all in good category. It is hoped that the Prabumulih City Social Service will increase accuracy in the preparation of program activities that can be implemented in real terms so that there are no program failures in their implementation in the following years. Then the Social Service of Prabumulih City to pay more attention to the things that cause the difference between budget and realization so that the use of funds can be in accordance with what was budgeted. And in order to further improve financial performance from the non-financial side, it is hoped that the Prabumulih City Social Service will further improve the capabilities of its employees by providing education and training on a regular basis and of course supported by adequate infrastructure.